Modeling and Simulation of Polymerization Processes - Vivaldo-Lima, Eduardo; Mohammadi, Yousef (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is a compilation of nine papers published in Processes, in a Special Issue on "Modeling and Simulation of Polymerization Processes". It aimed to address both new findings on basic topics and the modeling of the emerging aspects of product design and polymerization processes. It provides a nice view of the state of the art with regard to the modeling and simulation of polymerization processes. The use of well-established methods (e.g., the method of moments) and relatively more recent modeling approaches (e.g., Monte Carlo stochastic modeling) to describe polymerization processes of long-standing interest in industry (e.g., rubber emulsion polymerization) to polymerization systems of more modern interest (e.g., RDRP and plastic pyrolysis processes) are comprehensively covered in the papers contained in this reprint.